Factors influencing time management skills among nurses in North West Bank, Palestine - Raj'a Nayef Zyoud (BMC, 2023)
Abstract Background In today's companies, time management abilities have grown as a significant predictor of nurses' success. Organizations have simplified their internal operations and flattened their organizational structures in an effort to increase productivity and cut expenses. As a result, successful time management skills are particularly crucial for nurses in recently restructured healthcare organizations. This study aimed at exploring factors influencing time management skills among Palestinian nurses. Methods Cross-sectional quantitative study of all nurses (715) working in private and government hospitals and primary healthcare centers in north Palestine was conducted. Time management skills were measured on a continuous scale using the Nursing Time Management Scale (NTMS), Arabic version. The scale measures various aspects of time management including goal setting, planning, scheduling, and organizing activities. The relationship between time management skills and background variables was assessed using the multivariate linear regression. Results The average total score for NTMS scale was 63.39 out of a total score of 90. This score indicates relatively good time management skills among the respondents. The multivariate linear regression results showed that females obtained slightly lower scores than males, coefficient = -2.36, p = 0.043. Nurses in primary care centers had significantly higher scores than nurses who work at hospitals, coefficient = 4.47, p = 0.004. The type of healthcare organization emerged as a significant factor predicting time management skills. Nurses in private hospitals had worse time management skills than nurses in government hospitals, coefficient = -12.27, p < 0.001. Nurse supervisors had better time management skills than staff nurses, coefficient = 4.01, p = 0.023. Nurses working in non-teaching hospitals had worse time management skills than nurses in teaching hospitals, coefficient = − 3.86, p = 0.001. Nurses who did not attend a time management course had worse time management skills than nurses who attended time management course, coefficient = − 4.05, p = p < 0.001. Conclusions Healthcare institutions should consider organizational and individual factors to improve the time management skills of their staff. Time management training interventions are proven and effective policies that are recommended to be adopted by all healthcare centers.